2015
DOI: 10.4102/sajbm.v46i4.104
|View full text |Cite
|
Sign up to set email alerts
|

The components of career capital and how they are acquired by knowledge workers across different industries

Abstract: The literature shows that the way in which knowledge workers manage their careers in the global economy has changed fundamentally in the last twenty years. Career capital is a tradable commodity between and within organisations which impacts both human resource managers and knowledge workers. There is insufficient empirical evidence of the components of career capital and how these are acquired and there has been a dearth of investigation as to whether career capital is managed differently in different industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…The emergence of the knowledge economy has heightened interest in the employability of knowledge workers and their ability to adapt to rapidly changing employment contexts. Most would agree that a country’s capacity for building a knowledge-based economy relies less on traditional resources such as capital and labor for wealth creation and growth, and more on the intellectual capital of knowledge workers who have the skills and capacities for contributing innovative products, services, and processes that create value to the company and client (De Beer, 2015; Du Toit, 2014; Sutherland, Naidu, Seabela, Crosson, & Nyembe, 2015; Tchamyou, 2016). Therefore, it is not surprising that organizations demand of knowledge workers to be highly adaptable to changing business conditions and to stay relevant by proactively managing their employability (Sutherland et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of the knowledge economy has heightened interest in the employability of knowledge workers and their ability to adapt to rapidly changing employment contexts. Most would agree that a country’s capacity for building a knowledge-based economy relies less on traditional resources such as capital and labor for wealth creation and growth, and more on the intellectual capital of knowledge workers who have the skills and capacities for contributing innovative products, services, and processes that create value to the company and client (De Beer, 2015; Du Toit, 2014; Sutherland, Naidu, Seabela, Crosson, & Nyembe, 2015; Tchamyou, 2016). Therefore, it is not surprising that organizations demand of knowledge workers to be highly adaptable to changing business conditions and to stay relevant by proactively managing their employability (Sutherland et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most would agree that a country’s capacity for building a knowledge-based economy relies less on traditional resources such as capital and labor for wealth creation and growth, and more on the intellectual capital of knowledge workers who have the skills and capacities for contributing innovative products, services, and processes that create value to the company and client (De Beer, 2015; Du Toit, 2014; Sutherland, Naidu, Seabela, Crosson, & Nyembe, 2015; Tchamyou, 2016). Therefore, it is not surprising that organizations demand of knowledge workers to be highly adaptable to changing business conditions and to stay relevant by proactively managing their employability (Sutherland et al., 2015). Understandably then, concerns about proactive career adaptation and self-perceived sustainable employability become prevalent innate or psychological organismic needs that play a necessary part in the optimal career development, growth, and well-being of knowledge workers (Engelbrecht, 2018; Greenhaus & Kossek, 2014; Jackson & Wilton, 2016; Nazar & Van der Heijden, 2012; Onyishi, Enwereuzor, Ituma, & Omenma, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Career capital may vary in different contexts depending on the working environment, it may calculate, it may be portable, and it can be applied to individual growth, including personal development (Brown and Wond, 2018). Sutherland et al (2015) revealed 27 career capital components and five groups in their study. These five groups consist of success-oriented personal characteristics, effective interpersonal characteristics, good reputation, flexibility and adaptation, technical skills.…”
Section: Career Capitalmentioning
confidence: 99%
“…With the career, the information hidden within the employees is transformed into organisational information.Career capital, put forward by DeFillippi and Arthur (1994), is the value created on a career through recognition in the external labour market and the internal labour market. According toLamb and Sutherland (2010), career capital is the collection of all personal qualities, knowledge, skills, work experiences, achievements and relationships of the individual and is obtained by gathering at different career levels.Developing skills, talents and competencies will contribute to career capital by creating career development(Sutherland et al, 2015). Career capital consists of individual resources and relationships related to the individual's career.…”
mentioning
confidence: 99%
“…In this paper, the interest, here, is in the consultant’s supporting role as an instrument of interaction, guidance, and cooperation in career management. Indeed, while studies indicate the increasing role of the agent in career management (Sutherland et al , 2015), the role of structures, such as the labour market, organisations, and networks (Bourdieu, 1979), cannot be neglected. In this context, career transition consultants seem to occupy a strategic place at the frontier between agency and structure (Tomlinson et al , 2013).…”
Section: Introductionmentioning
confidence: 99%